2020
DOI: 10.3390/w12102939
|View full text |Cite
|
Sign up to set email alerts
|

Size Distribution and Phosphate Removal Capacity of Nano Zero-Valent Iron (nZVI): Influence of pH and Ionic Strength

Abstract: Nano zero-valent iron (nZVI) has been considered as a promising material for groundwater remediation in the past few decades. The size distribution of nZVI is one of the main factors that influences its transport capability and remediation capacity. However, studies on the size distribution of nZVI under different environmental conditions are still limited. In this study, the influence of the pH (pH = 5, 7, 9) and ionic strength (IS = 0, 15, 30, 45 mM) on the size distribution of nZVI are investigated. The dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The nanoscale particle size in the chain provides its high specific surface area and reactivity with contaminants. 65 Furthermore, the surface of the synthesized RC-nZVI is covered by a transparent layer, as demonstrated by the TEM images, which serves as a capping and stabilizing agent to prevent RC-nZVI from agglomerating and plays a crucial role in improving its dispersion and stability as a basic constituent of green-synthesized nZVI. 57,66,67 In the current investigation, SEM images added more support to those of TEM and confirmed that the synthesized RC-nZVI was mostly granular with a spherical shape, as shown in Figure 2B.…”
mentioning
confidence: 93%
“…The nanoscale particle size in the chain provides its high specific surface area and reactivity with contaminants. 65 Furthermore, the surface of the synthesized RC-nZVI is covered by a transparent layer, as demonstrated by the TEM images, which serves as a capping and stabilizing agent to prevent RC-nZVI from agglomerating and plays a crucial role in improving its dispersion and stability as a basic constituent of green-synthesized nZVI. 57,66,67 In the current investigation, SEM images added more support to those of TEM and confirmed that the synthesized RC-nZVI was mostly granular with a spherical shape, as shown in Figure 2B.…”
mentioning
confidence: 93%
“…The same results were observed by Abdelfatah et al (2021) when nZVI was synthesized by plant seeds ( Ricinus communis) extract [ 14 ]. In general, most nanoscale particle sizes in a chain provide a high specific surface area and reactivity with contaminants [ 26 ]. The TEM images show that all the nZVIs are covered by a transparent layer.…”
Section: Resultsmentioning
confidence: 99%
“…Another reason that we wanted to be sure of compatibility is that both materials of the nZVI composite would have the same potential and dynamics shown in Fig. 4 ( [33][34][35] .…”
Section: Particle Size Distribution Of Nzvimentioning
confidence: 99%